Contribution to the knowledge of the water mite (Acari: Hydrachnidia) fauna of Croatia - New data and records from a permanent pool in the Dinaric karst region - Ivana Pozojević; Natalija Vučković; Valentina Dorić; Marina Šumanović; Ivančica Ternjej (Persian Journal of Acarology)
Ponds are small lentic waterbodies that lack the deep aphotic layer. They can be either perennial or temporary as well as of natural or anthropogenic origin. Despite their small size and isolated nature, they are often considered as reservoirs of biodiversity for neighboring ecosystems, and could in fact be considered as special ecotones that house numerous semi-aquatic species. Although relatively poorly researched, ponds have been shown to contribute to regional biodiversity as much as rivers or lakes. The great local diversity of these petite ecosystems was once again proven in a small perennial pond (approximately 25 meters long and 10 meters wide) in the Dinaric Western Balkan ecoregion, where four water mite species were recorded, three of which are new findings for the water mite fauna of Croatia. Habitat conditions, i.e. macrophyte coverage and environmental water properties of the pond, proved to be suitable for typical pond species such as Piona laminata but also seemed to reflect conditions similar to helocrenes as species usually associated with these spring habitats were also found: Hydryphantes armentarius and Tartarothyas romanica.